STUDENTS’ NEED ON CREATIVE WRITING BASED – CHILDREN LITERATURE COURSE FOR EFL COLLEGE LEARNERS - Leni Marlina; Don Narius (SALEE: Study of Applied Linguistics and English Education, 2020)
It is a big challenge to college language study programs in developing courses designed to equip students with the competencies that can be used to take part in the creative industries for instance creative writing. This research aims to find problems and to gather informasi needed to develop teaching-learning materials of creative writing based Children Literature course for EFL college students. This course is necessary to be developed in accordance to the need of creative writing as part of creative industry in responding the trend of world economy whish is lead to the creative industry. To develop teaching-learning materials of creative writing based Children Literature course effectively, the first research needed is to conduct students’ need analysis by using questioner. This article describes (1) students’ problems in understanding explanations of concepts and examples of Children Literature; (2) students’ responses to the importance of various topics in the course of Children Literature; (3) students problems in learning subjects of Children Literature; (4) students’ responses to the importance of diverse exercises and tasks in Children Literature; (5) students’ responses to topics related to creative writing and Children Literature; (6) students’ need to the media of learning creative writing-based Children Literature course.